1996
DOI: 10.1093/oxfordjournals.humrep.a019199
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis: Leuprolide in a 3-monthly versus a monthly depot formulation for the treatment of symptomatic endometriosis: a pilot study

Abstract: An open-label randomized pilot study was conducted to evaluate the efficacy and acceptability of 6 months treatment with leuprolide in a 3-monthly versus a monthly i.m. depot injection for the relief of chronic pelvic pain in women with endometriosis. A total of 30 women aged 18-38 years were allocated to the 3-monthly depot arm (n = 15) or to the monthly depot arm (n = 15) after laparoscopic diagnosis of pelvic endometriosis. Mean (SD) deep dyspareunia scores according to a 0-3 point verbal rating scale decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…There appears to be no published literature that directly compares leuprolide acetate and buserelin acetate in endometriosis, but a review by the Cochrane Collaboration [25] suggests that, in similar trials, 24 weeks of treatment with buserelin acetate was associated with twice the BMD loss that was seen with leuprolide acetate [53,54]. However, these trials were conducted in different ethnic groups and the methods used for BMD analysis differed.…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be no published literature that directly compares leuprolide acetate and buserelin acetate in endometriosis, but a review by the Cochrane Collaboration [25] suggests that, in similar trials, 24 weeks of treatment with buserelin acetate was associated with twice the BMD loss that was seen with leuprolide acetate [53,54]. However, these trials were conducted in different ethnic groups and the methods used for BMD analysis differed.…”
Section: Discussionmentioning
confidence: 99%
“…Many descriptive studies have concluded that add-back HRT in the form of estrogens or estrogen plus progesterone is protective against bone loss. 43,44 Endometriosis and surgical menopause There appear to be significant variations in terms of surgical management especially in those women undergoing a hysterectomy for known, longstanding endometriosis. The dilemma arises in relation to the simultaneous removal of the ovaries as most of these women are young.…”
Section: Medical Menopause and Hormone Replacement Therapymentioning
confidence: 99%
“…Many descriptive studies have concluded that add-back HRT in the form of estrogens or estrogen plus progesterone is protective against bone loss. 43,44…”
Section: Medical Menopause and Hormone Replacement Therapymentioning
confidence: 99%
“…Infertility is defined as the failure to conceive after one year of regular unprotected intercourse, and prevalence is approximately 10 %-15 % in Western countries [1]. The demand for infertility services is steadily increasing, and so is the average age of women undergoing in vitro fertilization (IVF) [2, 3].…”
Section: Introductionmentioning
confidence: 99%